Stenotrophomonas maltophilia Pseudo-outbreak at a University Hospital Bronchoscopy Unit in Turkey - Ece, G (West Indian Med J, 2014)
OBJECTIVE: Stenotrophomonas maltophilia is an opportunistic pathogen found predominantly in the enviroment and hospital setting. Invasive procedures and treatment methods, instruments used for diagnosis and irrational antibiotic use play major roles in the spread of this pathogen. The study aimed to evaluate consecutive S maltophilia isolation from bronchoalveolar lavage samples during bronchoscopy procedure during a week. METHODS: Four patients consecutively had S maltophilia isolated during bronchoscopy between September 8 and 15, 2012. The identification of the isolates and their antibiotic susceptibility were studied by automated Vitek version 2.0 (Biomerieux, France) system. The clonal relationship between the isolates was studied by enterobacterial repetitive intergenic consensus (ERIC) polymerase chain reaction (PCR). RESULTS: Four consecutive S maltophilia isolates had identical band patterns and showed clonal relatedness. CONCLUSION: Bronchoscopy is a common invasive procedure that is utilized in chest diseases departments and intensive care units (ICUs). Contamination may take place due to inappropiate use and cause spread of infectious pathogens. In the current study, we detected consecutive S maltophilia strains with identical band patterns isolated within a week. After appropiate disinfection and cleaning procedures, no further isolation was detected.